A review of the Subtribe Lebiina Bonelli (Lebiini, Carabidae, Coleoptera) from Southwest of Saudi Arabia - Rasool, Iftekhar; Abdel-Dayem, Mahmoud S.; Felix, Ron F.f.l.; Aldhafer, Hathal M. (Zootaxa, 2018)
In this paper, descriptions, illustrations, distributional maps and a key for the subtribe Lebiina Bonelli, 1810 of Lebiini are presented for the two genera, Lebia Latreille, 1802 and Matabele, Peringuey, 1896 and six species from the southwest of Saudi Arabia. Lebia raeesae sp. n is described as a new species, L. melanacra (Chaudoir, 1878) and L. melanura (Dejean, 1831) are new records to the fauna of the country. Thus, the Saudi fauna of Lebiina based on this study has increased from three to six species.